The Marketing Mix for A Series of Wine Products Produced By S.C. Agroindustriala Bucium S.A. Iași - Cristian DELIBAS; Mioara MIHAILA; Andy-Felix JITAREANU; Maria BOGUS (ROBU); George UNGUREANU; Elena LEONTE; Mioara MIHAILA (Communications of International Proceedings, 2022)
This paper aims to combine two representative topics for the agri-food market: the wine market and the mix of marketing. Being oriented to the modern marketing, the main objectives are to explain how the marketing mix can be applied for the wine market, how is possible to create a sustainable and long-term relation offer-demand, and in which manner is possible to develop the vitality of this market. In this regard, it was approached a case study for one of the most important wine producers in Romania, with transposition of the marketing mix components in correlation with the success of the SC Agroindustriala Bucium SA company. The research methodology is based on a descriptive analysis with data collected from the company and the interpretation in a modern marketing vision. The results of the paper support the hypothesis that the modern marketing applied for the wine market is a necessity and a way to keep the success and longevity of a company with a special profile, like the wine production and winery.
Keywords: Marketing Mix; Market Share; Wine Promotion; Competitiveness